Taxodium mucronatum - one of the Fastest Growing Conifer in Doon - Vaid, K. M. (Indian Forester, 1967)
Taxodium mucronatum is an exotic conifer of Mexican origin which is a long-lived, fast growing tree, inhabiting wet soils along stream banks and attaining enormous girth of the trunk. Its performance as a successful introduction in Dehra Dun has been very commendable and has stood the test of the time. It seems to satisfy practically all the essentials for choosing a fast growing species - it is well suited to the conditions of soil and climate and the growth is healthy and vigorous with a good survival value. In about 35 years the trees have attained an enviable girth of about 11 ft. and a height of about 70 ft . Its large-scale plantation over some other similar localitis and those posing special problems of afforestation like, heavy rainfall areas, canal banks, dam sites, etc have been suggested for trial. Wood properties are such that it can possibly be put to a great diversity of uses for which there is a lot of dearth and demand in the country. Its Potential as a raw material for paper industry has been suitably assessed and the results compare favourably with the chir pine (Pinus roxburghii). On the aesthetic side, it can open new vistas in beautifying the landscapes.